PENGARUH LEVERAGE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN - STEFANI MAGDALENA CHANDRA; INDRA ARIFIN DJASHAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The aim of this research is to provide empirical evidence about the effect of profitability, leverage, firm size, audit quality, firm age, board of commissioner, board of directors, audit comittee, and managerial ownership on earnings management. Population of this research are non-financial companies listed in Indonesia Stock Exchange from 2012-2016. The samples of this study are 310 data using purposive sampling method. This research uses multiple regression method for data analysis. The result of this research shows that board of commissioner have effect on earnings management but , leverage, firm size, audit quality, firm age, board of directors, audit comittee, and managerial ownership do not have effect on earnings management.